A liberdade como fundamento do sistema moral kantiano - Oliveira, Edezio Muniz de (Universidade do Vale do Rio dos Sinos, 2017)
This dissertation aims to study the Kantian moral system with beginning and emphasis on freedom as the foundation of morality and its application to legal decisions in the resolution of conflicts in the concrete case. This study of freedom begins with the analysis of the third antinomy in the Critique of Pure Reason, where Kant demonstrates that beyond causality by nature there is also causality by freedom as characteristic of rational beings in that they can initiate a sequence of effects independently of a cause previous. In the continuation, some concepts necessary to the understanding of the moral like: good will, duty, respect, possibility of the foundation of the moral, categorical imperative and fact of the reason were studied. This study was concluded with the verification of the possibility of applying these teachings to law and justice, especially with regard to judicial decisions. In order to achieve these objectives, research was done on the works of Kant and on the works and articles of his commentators, as well as some strictly legal doctrines, but with a focus on the application of morals in order to bring justice to decisions in order to question The possibility of judges being able to use discretion when judgments in a concrete case as a way to bring justice to decisions and also to verify the compatibility of these decisions in relation to Kantian morality.
Keywords: Liberdade; Respeito; Dever; Justiça; Discricionariedade; Freedom; Respect; Duty; Moral; ACCNPQ::Ciências Humanas::Filosofia